Analisis Sentimen Positif Terhadap Avoskin sebagai Eco Friendly Brand di Media Sosial X dan TikTok - Magrifatul Zania Maharani (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
. The Indonesian beauty industry continues to grow, marked by the emergence of many local skincare brands. Avoskin is a local skincare brand that is committed to "green beauty" with environmentally friendly products. This research aims to determine general positive sentiment, mentions, and specific positive sentiment towards Avoskin as an eco friendly brand on social media Data was collected from online communities using social media monitoring tools, namely Brand24. This research shows that there are 858 general positive sentiments, 2,564 mentions, and 28 specific positive sentiments towards Avoskin as an eco-friendly brand with related keywords. The final results of the research show that X and TikTok users still do not give full attention to Avoskin as a eco friendly brand. Keywords: , , ,